Eusideroxylon zwageri (Ulin) as Key Species in Two Zones of Sangkima Rain Forest, Kutai National Park, East Kalimantan - Jehan Ramdani Haryati; Intan N. Azizah; Endang Arisoesilaningsih (Journal of Tropical Life Science, 2010)
Aim of this research was to study trees' diversity quality in primary and intensively used forest of Sangkima area in Kutai National Park (TNK), East Kalimantan (Borneo). Field observation was carried out by vegetation analysis using 17 sampling plots of 25x25 m2. Community structure of each forest was determined by calculating trees' density, basal area, frequency, important value and stratification of species. While trees diversity was estimated by taxa richness, Shannon-Wiener diversity index, and rate of endemism. Both forests were compared by Morisita community similarity index. Data were tabulated by Microsoft Excel 2007 and statistically analyzed by PCA method and supported by hierarchical cluster analysis in SPSS 15.00 for windows. The result showed that diversity quality in primary and intensively used forest of Sangkima TNK was high, indicated by similar stratification. The forests were composed by A stratum trees of > 30 m high to ground cover plants, but they were dominated by B stratum trees of 20-30m high. Primary forest's formation was Eusideroxylon zwageri-Mixed Dipterocarpaceae, while intensively used forest's formation was E. zwageri. Taxa richness of both forests was not different significantly. In the primary forest was found 34 species, 25 families and 16 orders, while intensively used forest was found 36 species, 20 families and 13 orders. Diversity Index of primary forest (H=4.57) was slightly higher than secondary forest (H=4.28). Rate of endemism of both forests reached 100%. Eusideroxylon zwageri and Cananga odorata were co-dominant in the Borneo rain forest. Tree of E. zwageri showed a biggest trunk and largest canopy. Cananga odorata showed a high density in both zones. Luxurious jungle performed A to E strata, but B stratum was dominant. Based on those five characters, trees' diversity quality in Sangkima was still high. Bi plot analysis showed that trees' community structure of both forests composed by three groups. In secondary forest, E. zwageri was a key species and characterized by high important value, while species C. odorata, Dyospiros borneensis and Dillenia beccariana found in a high distribution, otherwise other trees were classified into the 3rd group. Comparing to the secondary forest, even though E. zwageri was also as dominant tree, but the virgin one showed more species growing in a better density, distribution and dominance.Keywords: Tree, Borneo, rain forest, community structure, quality diversity, Kutai National Park